البنية الزمنية في شعر ابن دانيال: مقاربة في ضوء البنية الدالة الغولدمانية /Temporal Structure in Ibn Daniel’s Poetry in View of Lucien Goldmann’s Semantic Structure - ABEER A AL-Abbasi; Ibtisam Sati H Alharthi (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: هذه الورقة العلمية تسلط الضوء على "صورة الزمن" في النصوص الشعرية للشاعر ابن دانيال (1249-1311م)، للكشف عن "البنية الدالة" في أشعاره، من خلال توظيف مدلول "الفهم" باعتباره إحدى أدوات البحث الأساسية والأولية في المنهج البنيوي التكويني الذي أسس له الناقد الفرنسي لوسيان غولدمان (1913-1970م). جدلية البحث مفادها أن توظيف ابن دانيال للبنيات الزمنية في نصوصه لم يأتِ اعتباطاً، وإنما عن وعي بالعلاقة الجدلية بين الزمن بوصفه حقبة تاريخية، والزمن بوصفه مصدر إلهام؛ حيث يمازج ابن دانيال بين المفهومين لخلق ثيمات شعرية، ذات مضامين تعبيرية عن واقع حياة معيش. والدراسة بهذا المنظور تهدف إلى إثبات علاقة من تأثير متبادل بين لحظة الخلق الإبداعي لبنى ابن دانيال الزمنية، وسياقاتها الاجتماعية المعيشة من قبل فئة العُمَّال والحِرفية تحديداً، لإثبات أثرها في خلق مفاهيم زمنية ذات صلة بالحقبة الزمانية والمكانية المتمظهرة في العصر المملوكي بمصر تحديداً، وأثر هذه "الزمكانية" في خلق بنية تصورات ثيماته الشعرية، ودوافعها المجلية عن بنية دالة، كاشفة عن رؤية مبدع العمل لعالمه، ومنهج الدراسة هذه يتبع المنهح الوصفي التحليلي. توصلت الدراسة إلى أن بيتة الدالة قد تشكلت مزدوجة المعايير، واستعان بها في التعبير عن صورة الزمن في ذهنه التي أضفى عليها ملامح متضادة من مثل: غياب البقاء وحضور الفناء، وجدب الواقع وخصب الخيال، وطوباوية الوصال ودوستوباوية الهجران، وسيكولوجية الاغتراب وسيسولوجية الاستقرار، وجاءت بنيات العمل الصغرى في نصوص ابن دانيال في حالة انسجام تام بين بعضها بعضاً. الكلمات المفتاحية: ابن دانيال، لوسيان غولدمان، الفهم والشرح، البنية الدالة، الزمكانية. Abstract This scientific paper sheds light on the "image of time" in the poetic texts of the poet Ibn Daniyal (1249-1311 AD), to reveal the "structure-function" in his poems, by employing the meaning of "understanding" as one of the basic and primary research tools in the structural-formative approach that was founded by the French critic, Lucien Goldmann (1913-1970 AD). The argument of the research is that Ibn Daniyal’s use of temporal structures in his texts did not come arbitrarily, but it is rather out of awareness of the dialectical relationship between time as a historical period and time as a source of inspiration; where Ibn Daniel mixes between the two concepts to create poetic themes, with expressive contents about the reality of a relived life. From this perspective, the study aims to prove a relationship of mutual influence between the moment of creative creation of Ibn Daniyal’s temporal structure and its social contexts of living by the class of workers and craftswomen in particular. This is to prove its impact in creating temporal concepts related to the temporal and spatial eras that appeared in the Mamluk era particularly in Egypt. This study also investigate impact of this "spatio-temporal" in creating the structure of the perceptions of his poetic themes and their motives manifested from the structure-function, revealing the vision of the creator of the work for his world. The methodology of this study adopts the descriptive analytical approach. The study concluded that his line of poetry was formed by multiple standards. Ibn Daniyal used it to express the image of time in his mind, to which he gave contradictory features, such as: The absence of viability and presence of annihilation, deserted reality and fertile imagination, unity in utopian society and abandonment in dystopian society, and the psychology of alienation and the psychology of stability. The minor structure of work in the texts of Ibn Daniyal came in perfect harmony with each other. Keywords: Ibn Daniyal, Lucien Goldmann, understanding and explanation, meaningful structure, spatio-temporal. Abstrak Kajian ini membahaskan tentang "imej masa" dalam teks puisi penyair Ibn Daniyal (1249-1311 M), bagi mendedahkan "struktur semantik" dalam puisinya, dengan mengaplikasikan konsep "pemahaman" sebagai salah satu alat penyelidikan asas dan utama dalam pendekatan strukturalism genetik yang diasaskan oleh pengkritik asal Perancis iaitu Lucien Goldmann (1913-1970 AD). Dialektik kajian ini menyatakan bahawa penggunaan struktur masa oleh Ibn Daniyal dalam teksnya tidak digunakan dengan sewenang-wenangnya, sebaliknya ia digunakan atas kesedaran tentang hubungan dialektik antara masa sebagai zaman sejarah dan masa sebagai sumber inspirasi di mana Ibn Daniel menggabungkan antara dua konsep untuk mencipta tema puisi yang mengungkapkan tentang realiti kehidupan sebenar. Bertitik tolak dari perspektif ini, kajian ini bertujuan membuktikan wujudnya hubungan yang terhasil dari pengaruh bersama antara detik penciptaan kreatif bagi struktur masa Ibn Daniyal dan konteks sosial yang dialami oleh golongan pekerja dan kemahiran khususnya. Ini bagi membuktikan kesannya dalam mencipta konsep masa yang berkaitan dengan era masa dan tempat yang muncul pada era Mamluk di Mesir khususnya. Kajian juga bertujuan membuktikan kesan konsep "masa-tempat" ini dalam mewujudkan struktur persepsi tema puitisnya dan motif yang menzahirkan struktur semantik. Ini bagi menonjolkan sisi pandang pencipta karya terhadap dunianya. Kajian ini menggunakan pendekatan deskriptif dan analitikal. Kajian menyimpulkan bahawa struktur semantik puisi Ibn Daniyal terbentuk dengan piawaian berganda. Beliau menggunakan struktur ini bagi menyatakan imej masa dalam fikirannya, yang memberikan ciri-ciri yang bertentangan seperti: tiadanya kelangsungan hidup- wujudnya kemusnahan, kemandulan realiti - kesuburan imaginasi, hubungan dalam dunia utopia – retaknya hubungan dalam dunia distopia, sisi psikologi kehidupan perantauan- sisi psikologi kehidupan di negara sendiri. Karya kecil dalam teks Ibn Daniyal adalah harmoni yang sempurna antara satu sama lain. Kata Kunci: Ibn Daniyal, Lucien Goldmann, kefahaman dan penerangan, struktur semantic, aspek masa-tempat.